Kerajaan Malay political culture on the eve of colonial rule - Milner, Anthony Crothers, 1945- (2016)
A pioneering, provocative study of Malay political thought on the eve of colonial rule - based on both Malay and European source materials, and addressing issues that continue to be critical in Malaysia today. Focusing on both the Malay peninsula and North Sumatra, Kerajaan is innovative in approach - an historical investigation informed by methodologies developed in anthropology and literary criticism. The book argues that such close analyses of non-Western social thought are essential to achieve a genuinely global history, addressing the full variety of human perspectives and experience. In 2003 the US Association for Asian Studies selected Kerajaan as one of the 25 'works of major importance to historical studies' and 'most frequently cited in the literature' in the field of Southeast Asian history.